Association between depression and diabetes among American adults using NHANES data from 2005 to 2020 - Chuanjie Zheng; Jianming Yin; Linyue Wu; Zhanhui Hu; Yikai Zhang; Lingyong Cao; Yiqian Qu (Scientific Reports)
Abstract Depression impairs self-management in diabetic patients, exacerbates insulin resistance, and elevates glycated hemoglobin (HbA1c) levels, thereby increasing diabetes risk. This study analyzed data from 30,386 participants in the National Health and Nutrition Examination Survey (NHANES), assessing depression severity using the 9-item Patient Health Questionnaire (PHQ-9) and evaluating diabetes status through clinical markers such as HbA1c, random blood glucose, and fasting blood glucose. Participants were stratified by depression severity and diabetes status to examine the relationship between depression and diabetes risk. We applied descriptive statistics, logistic regression models, subgroup analyses, and restricted cubic spline (RCS) modeling to explore this association. The results revealed that greater depression severity was significantly associated with increased diabetes incidence, elevated HbA1c, fasting glucose, and insulin levels. Multivariate regression analysis confirmed a consistent positive correlation between depression severity and diabetes risk. Subgroup analyses further identified significant relationships between depression and various demographic and behavioral factors, including gender, race, BMI, smoking status, and prediabetic conditions. Additionally, the RCS model demonstrated a clear increase in diabetes risk with rising PHQ-9 scores. In conclusion, our study demonstrates that the severity of depression is positively correlated with the risk of diabetes, and this association may be closely linked to various glycemic and lipid metabolic parameters.